PM10-Associated Heavy Metals and Health Risk Assessment in Charcoal Production Communities: A Case Study in Phitsanulok Province, Thailand - Srithawirat, Thunwadee; Jupu, Sakultala; Raksuan, Sirirat; Noinumsai , Supawadee (Journal of Food Health and Bioenvironmental Science, 2024)
This research aimed to assess the concentration and health risks associated with exposure to particulate matter less than 10 microns in diameter (PM10) in charcoal production communities in Phitsanulok Province. The study area was divided into two zones: residential and charcoal kiln areas. Samples were collected using a personal sampling pump, and the concentrations of heavy metals (Zn, Fe, Cd, Cu, and Pb) in the PM10 samples were determined using flame atomic absorption spectroscopy (FAAS). The results showed that the average concentration of PM10 in the kiln zone exceeded both Thailand's National Ambient Air Quality Standards (NAAQS) and the World Health Organization (WHO) recommendations. The mean concentrations of metals in PM10 were ranked as follows for the kiln zone: Fe (107.87 ng m-3 > Zn (86.83 ng m-3) > Pb (65.20 ng m-3) > Cu (17.39 ng m-3) > Cd (5.07 ng m-3). In the residential zone, the mean concentrations of Fe, Zn, Pb, Cu, and Cd were 12.59, 16.43, 7.09, 1.86, and 1.08 ng m-3, respectively. All heavy metals were found to be well within the permissible safe limits set by the US. EPA, except for Cd. The health risk assessment, based on the Hazard Quotient (HQ), revealed HQ values ranging from 0.83 to 11.26 in the residential area and from 1.87 to 14.41 in the kiln area, both of which are greater than 1.0, indicating potential human health risks.